2020
DOI: 10.1177/0887403420980806
|View full text |Cite
|
Sign up to set email alerts
|

Do Released Prisoners’ Perceptions of Neighborhood Condition Affect Reentry Outcomes?

Abstract: As the United States enters a decarceration era, the factors predicting reentry success have received a rapidly growing body of research attention. Numerous studies expand beyond individual-level attributes to assess the contextual effect of neighborhoods to which released prisoners return. However, past studies predominantly used neighborhood structural/economic characteristics as the proxies of neighborhood context, leaving the roles of community cohesion and disorder understudied in the context of reentry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Numerous social, as well as individual, factors have been studied in relation to criminal activity and desistance from crime. Some of these factors include employment (Liu et al, 2020), race (Rocque et al, 2019), and geographic location (Aksoy, 2017). Marital status is one factor that is increasingly being studied by criminologists to understand how marriage relates to criminality and desistance from criminal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous social, as well as individual, factors have been studied in relation to criminal activity and desistance from crime. Some of these factors include employment (Liu et al, 2020), race (Rocque et al, 2019), and geographic location (Aksoy, 2017). Marital status is one factor that is increasingly being studied by criminologists to understand how marriage relates to criminality and desistance from criminal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Family matters. Many released prisoners will reconnect (or attempt to reconnect) with parents, spouses, former spouses, and children (Liu et al, 2020d;Uggen et al, 2001). Family can provide much-needed prosocial ties (McKiernan et al, 2013;Naser & La Vigne, 2006;Phillips & Lindsay, 2011), help released prisoners re-establish themselves in society (Uggen et al, 2004), and offer a level of supervision and accountability for released prisoners (Western et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies that controlled respondents’ prior mental health conditions also reported a significant association between concerns over neighborhood environment and mental health outcomes (Latkin & Curry, 2003; Liu et al, 2020). For example, after adjusting for baseline levels of depressive symptoms, Latkin and Curry (2003) found that perceptions of neighborhood deviance and crime issues (i.e., vandalism, litter or trash, burglary, drug selling, and robbery) still held significant predictive power on depressive symptoms at a nine-month follow-up interview.…”
Section: Introductionmentioning
confidence: 99%